Acceleration of Biodiesel Production - Pulidindi, Indra Neel; Gedanken, Aharon (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The development of renewable energy sources will help alleviate the twin problems of energy appetite and environmental pollution. Among such renewable sources, biofuels standout. Biodiesel is at the top of the list of biofuels that have the potential to substitute conventional fossil-based transportation fuels. The reprint comprises 11 chapters in total dealing with a variety of feedstock needed for the sustainable production of biodiesel, various catalysts that could be used for the accelerated production of biodiesel, and advances in reactor technology for the demand-based production of biodiesel. Indebtedness is due to various research groups, namely: Fahad Rehman and co-workers from Pakistan, Qatar, and the UK; Tao Lyu and co-workers from the UK, China, and Germany; Sandro L. Barbosa and co-workers from Brazil and the USA; Anita Salic and co-workers from Croatia; Fabrizio Roncaglia and co-workers from Italy; Jose C. S. dos Santos and co-workers from Brazil; Anoop Singh and co-workers from India and Brazil; Dhurba Neupane from the USA; Zhang and Wang and co-workers from China; and Awogbemi and Kallon from South Africa for their scholarly work that enabled the publication of this reprint on "Acceleration of biodiesel production".